Problems and realities in protecting the Strategic Agriculture and Fisheries Development Zones (SAFDZ) of a rapidly developing regional urban center the case of San Fernando City, Pampanga - Mendoza, Agustin C (2007)
Some of the problems and realities in protecting and preserving the agricultural lands of a rapidly developing regional urban center particularly the case of San Fernando City (P.) were determined. Analysis of the situation was focused both at the regional and urban level...
" October 2007."
Thesis (M.A. Urban & Regional Planning)--University of the Philippines Diliman.
Keywords: Agriculture -- Economic aspects -- Philippines -- San Fernando City (Pampanga).; Fisheries -- Economic aspects -- Philippines -- San Fernando City (Pampanga).; Land use -- Philippines -- San Fernando City (Pampanga).